Some population parameters of Garra rufa (heckel, 1843) in Murat river - Aslan, Şaban; Yüksel, Fahrettin; Çoban, Mehmet Zülfü (Centenary University, 2021)
This study conducted to determine some population parameters of Garra rufa (Heckel, 1843) known as doctor fish living in Murat River. A total of 322 fish sample examined in the study was caught by using cover net and electro-shocker between March 2016 and February 2017 in the Murat River. The female-male rate of population consisting of I-V age groups was confirmed as 1: 1.24. The regression coefficient (b) in the length-weight relationship was determined as 2.4551 (negative allometric) for females, as 2.2039 (negative allometric) for males and as 2.3167 (negative allometric) for all individuals. The total lengths and weights of examined fish samples were varied from 5.1 cm to 15.5 cm and from 3.0 g to 50.6 g, respectively. Mean condition factor of all age groups of populations was calculated as 1.17. Growth parameters of population were calculated as L? = 16.33 cm, K = 0.37 year-1, t0 = -0.18 year, W? = 42.59 g for female, as L? = 15.25 cm, K = 0.43 year-1, t0 = -0.03 year, W? = 31.37 g for male and as L? = 15.88 cm, K = 0.39 year-1, t0 = -0.13 year, W? = 36.62 g for all population. Growth performance index (?) was calculated to be 4.59 for female, to be 4.61 for male and to be 4.59 for both. © 2021, Centenary University. All rights reserved.
Murat nehri?deki Garra rufa (heckel, 1843)?ın bazı populasyon parametreleri
Keywords: Age; Garra rufa; Growth; Murat river; Population